Waiting time and quality of care in operated odontostomatology patients - Gutierrez, Alejandro (2019)
Introduction: Waiting times for elective surgery are indicators that legitimize socially public health services, if their situation is appropriate. Objective: To determine the relationship between the waiting time and the perception of the quality of care in Odontostomatology patients of a Social Security hospital. Methods: Satisfaction and dissatisfaction levels were determined by means of the modified SERVQUAL instrument, the results were correlated with the waiting time of more than 180 days and the quality of life; was affected, as well as which of these factors was most influenced about the degree of dissatisfaction. Results: The degree of satisfaction was 44%. The patients who waited more than 180 days presented 2.6 times more possibility of dissatisfaction, the affected patients presented 3.4 times more possibility of dissatisfaction. Finally, the affected patients presented 3.3 more possibilities of dissatisfaction, in relation to those who waited more than 180 days, which presented 2.5 more possibilities of dissatisfaction. Conclusion: There is an inverse relationship between waiting time and the perception of quality of care; In addition, the degree of dissatisfaction is associated, above all, with the impact of the quality of life rather than the waiting time itself.